Prevalence and risk factors associated with fasting blood glucose levels in adults aged 30 years and older with disabilities: the results from an annual health check-up. (April 2014) - Lin, Jin-Ding; Lin, Lan-Ping; Lee, Jiunn-Tay; Liou, Shih-Wen; Chen, Yu-Jung; Hsu, Shang-Wei; Liu, Chien-Ting; Leu, Yii-Rong; Wu, Chia-Ling
<x content-type="archive" xml:space="preserve">Abstract</x> The purpose of this study was to collect information on the fasting blood glucose (FBG) profile in individuals with disabilities and to determine associated risk factors in this population. This study was a cross-sectional survey of 833 adults with disabilities who were 30 years of age or older and who voluntarily participated in the 2010 annual health examination provided by a local government in east Taiwan. The results demonstrated that 23% of participants had prediabetes (FBG: 100–125 mm/dl), and 10·7% participants had diabetes (FBG>126 mm/dl). The findings appear to demonstrate that individuals with disabilities experience a higher prevalence of diabetes than the general population, and greater attention must be paid to this population within the healthcare system. In the logistic regression model, older age, and body mass index (BMI) were predictive of diabetes in this population. In addition, elderly individuals (OR = 5·96, 95% CI = 1·67–21·23) or those from 44 to 64 years (OR = 6·67, 95% CI = 1·94–22·97) with a disability were more likely to have diabetes than were younger individuals (30–44 years of age). Overweight or obese subjects were more likely to have diabetes compared to the underweight group (OR = 7·08, 95% CI = 2·11–23·76). To decrease the risk of diabetes in individuals with disabilities, health authorities should initiate effective preventive interventions and prepare for the detection, management and complications of diabetes.